Metal foaming by powder metallurgy process: investigation of different parameters on the foaming efficiency - Ioannis Papantoniou; Helena Kyriakopoulou; Dimitrios Pantelis; Dimitrios Manolakos (Fracture and Structural Integrity)
Aluminium foams, produced by powder metallurgy process, have significant potential applications for uses in weight-sensitive structural parts. Problems in the production of metal foams arise from the lack of knowledge in the control of process parameters. The results are frequently uneven and unpredictable variations in the structure and properties of the final foamed parts are observed. This paper aims to investigate the effect of different parameters of the powder metallurgy with foaming agents process on the foaming efficiency. The parameters examined included the powder morphology, the compaction pressure and the foaming temperature. During the foaming stage, for each set of parameters the porosity-time (Pf-t) diagrams were created and the foaming efficiency was calculated (η=Pfmax). Results indicated that the highest foaming efficiency was observed at the specimens with the fine aluminium powder, with high (700 MPa) compaction pressure and high foaming temperatures (800 oC). Finally, compression tests were performed on the foamed specimens with the higher foaming efficiency in order to investigate their s-e response. Furthermore, average compressive strength and density were estimated and presented.